1995
DOI: 10.1017/s025292110002279x
|View full text |Cite
|
Sign up to set email alerts
|

Rotation Curves of 38 Galaxies in Clusters from Scanning Fabry-Perot observations

Abstract: Abstract.A major astrophysical problem is related to the fact that rotation curves (RCs)) of galaxies are flat. The presence of a dark halo is most often invoked to explain that. Some controversies exist concerning the existence of a dark halo for galaxies in very hostile environments like in center of clusters. Using a scanning Fabry-Perot interferometer, we have observed Ha velocity fields of a sample of 38 galaxies located in 7 different clusters of galaxies. From this sample, our conclusion is that spirals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
56
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(61 citation statements)
references
References 3 publications
5
56
0
Order By: Relevance
“…It shows more H i flux on the higher velocity side, in agreement with the optical rotation curve. The optical velocity map of Amram et al (1992) further confirms the observed asymmetry in the H distribution. The I-band image suggests an increase in flux in front of the nucleus (as does that of UGC 8096/IC 3949).…”
Section: Populationsupporting
confidence: 71%
“…It shows more H i flux on the higher velocity side, in agreement with the optical rotation curve. The optical velocity map of Amram et al (1992) further confirms the observed asymmetry in the H distribution. The I-band image suggests an increase in flux in front of the nucleus (as does that of UGC 8096/IC 3949).…”
Section: Populationsupporting
confidence: 71%
“…See also Bertola & Capaccioli (1977) and Emsellem & Arsenault (1997) for NGC 128. Nine galaxies have available ionized-gas rotation curves, all of them measured from H: IC 4767 (Rubin, Whitmore, & Ford 1988;Amram et al 1995), NGC 1886, NGC 2788A, IC 2531, ESO 443-G042, ESO 240-G011 (Mathewson, Ford, & Buchhorn 1992), NGC 4469, NGC 4710 (Rubin, Waterman, & Kenney 1999), and ESO 597-G036 (Nishiura et al 2000). We note that Bureau & Freeman (1999) did not extract rotation curves from their data, relying instead on the entire PVD diagrams.…”
Section: Comparison With Published Datamentioning
confidence: 99%
“…Velocity maps derived using 3D spectroscopy reproduce the complete velocity field, contrary to longslit spectra. Hα observations using FP instruments have been used for some 40 years now (Tully 1974;Deharveng & Pellet 1975;Dubout et al 1976or de Vaucouleurs & Pence 1980; and have been designed to derive velocity fields of nearby galaxies (e.g., Atherton et al 1982or Boulesteix et al 1984, and to create high signal-to-noise ratio (S/N) rotation curves for many spiral galaxies (e.g., Marcelin, Boulesteix & Georgelin 1985;Bonnarel et al 1988;Pence, Taylor & Atherton 1990;Corradi & Capaccioli 1991;Amram et al 1992;Cecil, Wilson & Tully 1992;Amram et al 1994;Sicotte, Carignan & Durand 1996;Ryder et al 1998;Jiménez-Vicente et al 1999;Knapen et al 2000 and many more). Chemin et al (2006) presented an Hα FP survey of Virgo cluster galaxies.…”
mentioning
confidence: 99%